COVID-19 and Psychological Distress in Africa - Communitarian Perspectives - (:unkn) unknown (Routledge, 2024)
This timely book draws on unique African experiences to explore the intersection between mental health and African communitarianism in the context of COVID-19, giving voice to the perspectives of vulnerable populations facing pre-existing challenges such as depression, anxiety, and stress. Advancing knowledge and contributing to the global debate about the effects of the pandemic on the psychological well-being of African people, chapters critique the role of media, information, misinformation, and disinformation during this period on individual- and community-based mental health. Using a holistic approach, the book highlights the need to prioritise the localising of mental health systems and clinical services to provide a better standard of care and comprehensive, context-specific mental health interventions that consider the heterogeneity within and between African regions. The book demonstrates through nuanced evidence and analysis that communitarian perspectives allow African societies to balance collective solidarity with individual well-being to benefit overall mental health. Ultimately drawing on communal values and localised knowledge to cultivate resilience to fight the psychosocial impacts of COVID-19 in Africa, the book will be of interest to scholars, postgraduate students and researchers exploring psychology, philosophy of mental health, and public health policy more broadly, as well as and cultural studies and the sociology of pandemics. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Yamikani Ndasauka is Associate Professor in Department of Philosophy, University of Malawi, Malawi.
Edition 1st Edition First Published 2024 eBook Published 9 January 2024 Pub. Location London Imprint Routledge DOI https://doi.org/10.4324/9781003425861 Pages 272 eBook ISBN 9781003425861 Subjects Area Studies, Behavioral Sciences, Humanities, Social Sciences OA Funder University of Malawi
Keywords: Area Studies; Behavioral Sciences; Humanities; Social Sciences